Shariah Audit Practices in Malaysian Islamic Banks: An Audit Expectation-Performance Gap Analysis - Supiah Salleh; Mustafa Mohd Hanefah; Zurina Shafii; Muhammad Iqmal Hisham Kamaruddin (USIM Press, 2024)
Shariah Governance and Assurance in Islamic Financial Sectors (pp. 113-145). Negeri Sembilan: USIM Press, 2019